Use and Diversity of Palm (Arecaceae) Resources in Central Western Brazil - Renata Corrêa Martins; Tarciso de Sousa Filgueiras; Ulysses Paulino Albuquerque (The Scientific World Journal)
Arecaceae Schultz-Sch. (Palmae Juss.), a member of the monocotyledon group, is considered one of the oldest extant angiosperm families on Earth. This family is highly valuable because of its species diversity, its occurrence in a wide range of habitats, and its status as an integral part of the culture and the family-based economy of many traditional and nontraditional communities. The main objectives of this study were to perform an ethnobotanical study involving these palms and a “Quilombola” (Maroon) community in the municipality of Cavalcante, GO, Brazil. The variables gender, age, and formal schooling had no influence on the number of species recognized and used by the Kalungas. Ethnobotanical studies based on traditional knowledge in addition to use and management of palms are fundamental aspects for planning and appliance of public policies directed to the use of natural resources and improvement of life quality.